PEMBELAJARAN BAHASA ARAB DENGAN MENGGUNAKAN METODE SAM’IYYAH SAFAWIYYAH DI SD DINIYAH AISYIYAH, MENTENG BATA JAKARTA SELATAN - Kulsum, Umi; Hendra, Faisal (CV. Lafadz Jaya, 2024)
This research aims to determine the Arabic language learning media for fourth grade students at SD Diniyah Aisyiyah Menteng Bata, South Jakarta using the Sam'iyah Syafawiyah learning method which includes: the learning process in class, learning media, and to find out the extent of the learning stages carried out by the teacher through the use of media. Classroom learning uses the Sam'iyyah Syafawiyah method. And finally, to find out how teachers try to overcome inhibiting factors in the Arabic language learning process for fourth grade students at Diniyah Aisyiyah Elementary School, Menteng Bata, South Jakarta. This type of research uses a method (field research) taking the location at SD Diniyah Aisyiyah Menteng Bata, South Jakarta. Data collection was taken from the results of observations carried out directly in class, interviews. Data analysis uses qualitative descriptive techniques to explain the analysis results obtained. The results of this research show that the learning media in class IV of Diniyah Aisyiyah Elementary School using the Sam'iyyah Syafawiyah method is considered successful. This is viewed in terms of the active use of learning media using books, audio recordings and videos. Through the Sam'iyyah Syafawiyah method which is applied in the classroom, and the use of appropriate learning media helps students be active so that the Arabic language material delivered by the teacher in class can be understood by students.